Is gold investment a safe haven or a hedge for the Malaysian inflation? - M. S. M., Khair Afham; Law, Siong Hook; Wan Ngah, Wan Azman Saini (Universiti Malaysia Sarawak, 2017)
This study examines the long and short term abilities of gold to hedge against inflation in Malaysia during the period from 1971 to 2011. The Johansen cointegration results reveal that there is a long term relationship between gold price and consumer price index. Using the Tsay’s linearity test, the findings demonstrate the nonlinear relationship between gold return and inflation rate. Thus, the nonlinear threshold vector error-correction model (TVECM) analysis is employed to analyze the causal relationship and gold’s hedging ability in short term. Gold is proven to be effective as a hedging tool against inflation, but effectiveness varies on different price momentums (based on threshold) and the time period. It is found that during high momentum regimes, gold return is able to hedge against inflation in Malaysia better than during low momentum regimes.